Cognition, conscience, and creativity: multimedia-based literature teaching for pre-service teachers in Indonesia - Novita Dewi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
In this multimedia age, the goals of education are mostly geared toward increasing efficiency and productivity by producing young people to function in today’s global economy. This article would argue that it is also of vital importance to include humanism and reflection in education, for instance in literature teaching. To support this argument, this article presents a brief teaching report on multimedia utilization to teach short stories and novels with difficult, controversial themes for pre-service teachers in Indonesia using Ignatian Pedagogical Paradigm. Applying content analysis method, this descriptive-explanatory study investigates how multimedia can help the students to become creative and reflective at the same time. Involving 38 EFL students of a literature class, it observes teaching materials, students’ assignments, and reflection notes as data. This study shows that (1) multimedia can assist students to think beyond literature and expand their cognition; (2) the use of videos, web-based visual creators, and other multimedia resources can support students’ creativity; and (3) reflection remains an important aspect in literature teaching irreplaceable by multimedia sophistication. The conclusion is that multimedia is without doubt useful in literature teaching today on condition that its use helps enrich students’ multiple perspectives.